The use of multiple criteria decision making methodologies for the promotion of RES through funding schemes in Cyprus, a review - Florides, Georgios A.; Theodorou, Savvas; Tassou, Savvas A. (My University, 2010)
In isolated energy systems with no indigenous sources of energy such as the one of the Republic of Cyprus, the renewable energy option is the only alternative to achieve energy independence. Though, the relative technological maturity of renewable energy sources and their satisfactory efficiencies, their implementation has not reached the expected levels in many regions. This situation is mainly due to the fact that the up-to-date efforts for their development have been underestimated and the parameters involved in drafting subsidy schemes are in some cases misinterpreted and not given the appropriate attention. Decision makers are faced with ongoing major energy challenges such as fossil fuel depletion, increasing demand, energy prices and thus the move towards a sustainable energy development is crucial and highly complicated. This paper investigates the use of MCDM methods and then implements the methods for three subsidy schemes available in Cyprus
Keywords: Renewable energy resources; Fossil fuels; Natural resources; Cyprus